Analisis Prosedur Audit Kas Setara Kas BLUD Puskesmas X Oleh KAP ENHA - Puput Mia Ayuningtias; Diah Hari Suryaningrum (AKUNTANSI 45, 2024)
This research aims to analyze the cash equivalent audit procedures at the Regional Public Service Agency, Puskesmas X, which are implemented by the ENHA Public Accounting Office. The research method used is descriptive-qualitative with a case study approach, and the technical data analysis used is descriptive analysis, which is used to describe the cash equivalent audit procedures implemented by KAP ENHA. The cash equivalent audit procedure implemented by KAP ENHA consists of control and substantive tests. Substantive tests carried out by KAP ENHA are: comparing the cash equivalent balance in the financial report with the general ledger; carrying out cash taking; comparing the cash equivalent balance in the current account with the general ledger and trial balance; carrying out bank confirmations; making lead schedules or work papers; and evaluating the adequacy and disclosure of cash equivalents in BLUDs in the financial statements. The results of this research indicate procedures for implementing the audit of cash equivalents in BLUD Puskesmas disclosure of BLUD cash equivalents.